(untitled) (Philological Studies, 2019)
The collective group identity of the category known today as Makedonci Muslimani started with the process of conversion to Islam and segregation from Christian community. Thus, relations with the others, including those with the same linguistic origin, were built on the religious base. The national creation based on language, except for the Albanian example, found obstacles in the religious aspect, keeping the old division of Ottoman Millet system. The Christians in the Balkans understood the language of nationalism, but their attitude towards the Muslims was close to the domain of non-defined discourse between religious communities. On the other hand, because the Balkan Muslims couldn’t adapt to the national code, they were excluded from the process of national integration and homogenization, and they kept their fluent consciousness represented through the Millet mentality and the Ottoman heritage. Throughout the twentieth century, within the territory of the Republic of Macedonia today, the Serbian, Albanian and Macedonian nationalities were promoted through this group. The agency used the secularization of the society as the base for promoting the ethno-linguistic character of the national identities. Education and mass administration were the basic tools for indoctrination. In the post World War II period, that which gave substance to Makedonstvoto (the Macedonianhood), like the relations between the Christians and the Muslims, excluded the category of Makedonci Muslimani. For the Macedonians (Macedonians=Christians), the inherent conflict between the Orthodoxy, as the central element of their identity, and the Islam apriori excluded all the Muslims.